SAT-267 Pregnancy in Acromegaly: Report of Five Cases - Burcea, Iulia Florentina (J Endocr Soc, 2020)
Introduction: In acromegaly, there are changes in growth hormone (GH), insulin-like growth factor-1 (IGF-1) and insulin, hormones very important in pregnancy as well. Despite novel treatments, pregnancy in acromegaly is uncommon, remaining a challenge for clinicians. We report seven pregnancies in five women with acromegaly. Clinical Cases: Five acromegalic patients (17 – 35 years-old) underwent seven pregnancies. All patients had macroadenoma: four were submitted to non-curative neurosurgery and two of them had gamma-knife radiosurgery. One patient had medical treatment prior to curative transsphenoidal surgery (TSS). One patient being treated with estroprogestative for hypogonadism had a spontaneous pregnancy; three others had pregnancy just before biochemical diagnosis of acromegaly, one of them had also a spontaneous abortion and another successful pregnancy during treatment with somatostatin receptor ligand (SRL); the last patient become pregnant during treatment with SRL, prior to TSS. Monitoring was made with IGF-1, GH (assay with no distinction of pituitary GH versus placental GH), prolactin (PRL) and visual field; pituitary imaging was performed after pregnancies in all. All women conceived naturally, two being on treatment with SRL (discontinued after confirmation of pregnancy). No treatment for acromegaly was administered before delivery. All patients had physiologic pregnancies, delivered full-term healthy babies, no malformations or metabolic disruptions; one did not breast-feed; another one had a spontaneous abortion 2 days after confirmation of pregnancy. No patient developed either hypertension, pre-eclampsia or gestational diabetes. In three cases, the clinical suspicion of acromegaly had risen during pregnancy and the diagnosis was made 1 year after delivery. The one with three pregnancies had controlled secretion of GH on Lanreotide and GH and IGF-1 levels remained stable during pregnancy. The woman with gonadotroph deficiency after TSS and GK and substitutive therapy had a decrease in IGF-1 during pregnancy (45 %), which after delivery returned pathologically to before pregnancy values; GH levels remained stable. The last patient, who became pregnant with uncontrolled acromegaly on Pasireotide, had increased, but stable GH and IGF-1 (2 X upper limit of normal) before, during and after pregnancy. TSS performed 3 years after delivery cured the disease. Conclusion: From our experience, patients with acromegaly may have normal babies, even in patients with uncontrolled hypersecretion and lack of medical treatment during pregnancy. The consensus is, however, that there is no indication to use medication to control GH hypersecretion or tumor size in acromegaly patients during pregnancy (1). Reference: (1) Muhammad A, Neggers SJ, van der Lely AJ. Pregnancy andacromegaly. Pituitary. 2017;20(1):179–184. doi:10.1007/s11102-016-0740-3